Genetic screening of children with suspected inherited bleeding disorders. Issue 2 (26th February 2020) - Andersson, Nadine G.; Rossing, Maria; Fager Ferrari, Marcus; Gabrielaite, Migle; Leinøe, Eva; Ljung, Rolf; Mårtensson, Annika; Norström, Eva; Zetterberg, Eva
Abstract: Introduction: Genetic screening using high‐throughput DNA sequencing has become a tool in diagnosing patients with suspected inherited bleeding disorders (IBD). However, its usefulness and diagnostic efficacy in children is unclear. Aim: To evaluate the diagnostic efficacy of genetic screening for IBD in children and downstream further testing. Methods: After informed consent, children (<18 years) with suspected IBD underwent genetic screening with 94 selected genes. Results: A total of 68 heterozygous class 3‐5 variants were detected in 30 children, 2.3 variants per patient. Directed specific functional testing was performed after genetic screening in a subset of patients. Adhering to the ACMG guidelines, the results of functional testing together with family history and previous publications classified three variants as likely disease causing (class 4) and two variants as disease causing (class 5), all in children with thrombocytopenia. The overall diagnostic rate was 16.7% (5/30). Children with thrombocytopenia had a significantly higher rate of significant genetic findings, 5/9 (55.6%) vs. 0/21 (0%; P  = .0009). Conclusion: We conclude that performing genetic screening in children is an effective tool especially for children with inherited thrombocytopenia and has the possibility to diagnose platelet disorders adequately early in life. Children with bleeding diathesis, normal coagulation work‐up and without thrombocytopenia are unlikely to be diagnosed by genetic screening. Ethical issues such as incidental findings, variants associated with cancer and the interpretation of the genetic results into clinical practice remain problematic.